An investigation into the manifestation of stigma and discrimination and its consequences on HIV/AIDS prevention and treatment efforts amongst people living with HIV/AIDS - Chipangura, Sheila (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.